An increase in the retirement age in China: the regional economic effects. Issue 7 (7th February 2017) - Chen, Anping; Groenewold, Nicolaas
ABSTRACT: China's pension system is in need of comprehensive reform. One measure on which we focus is to increase the retirement age. It is likely that a change in retirement age will have significantly different effects across China's regions. Interregional disparities are already very substantial in China and it will be important to know how changes in pension arrangements will affect disparities. We consider four policies to increase the retirement age from 60 to 61. They differ according the use made of the extra revenue generated by the policy. All four policies increase welfare and reduce the interregional welfare gap.